Baptism of fire into the teaching profession : tips from the practicum. - Hussin, Habsah; Swaran Singh, Charanjit Kaur
The practicum is ESL (English as a Second Language) trainee teachers' debut into the teaching profession. Ideally, these trainee teachers should be looking forward to undertaking the practicum as it is the culmination of their study at the university and an avenue for them to hone their skills as teachers in app lying the knowledge gained, and translating theories in to practice appropriate to the context, and needs of their learners. As they are teaching in a 'real context' of the profession for the first time, the practicum is their 'baptism of fire' into the teaching profession and could prove to be an overwhelming experience for some of them . As such, they are bound to make mistakes (both serious and mild) which if not curbed and rectified, may affect their effectiveness in their teaching, In this paper, I am going to focus specifically on common mistakes made by trainee teachers in the early part of their practicum (before the interventions by their mentors and supervisors) in the planning stage and in implementing the lesson planned.